Analysis of the contrast between natural occurence of toxigenic Aspergillii of the Flavi section and aflatoxin B1 in cassava - Adjovi, Y.C.S.; Bailly, S.; Gnonlonfin, G.J.B.; Tadrist, S.; Querin, A.; Sanni, A.; Oswald, I.P.; Puel, O.; Bailly, J.D. (Elsevier, 2014)
Aflatoxin B1 (AFB1) is a carcinogenic mycotoxin produced by Aspergillii of the section Flavi that may contaminate food, in the field or during storage. Cassava represents an important staple food in sub-saharian Africa. The analysis of aflatoxigenic fungi in 36 cassava samples obtained from producers in Benin indicated that 40% were contaminated by Aspergillii of the section Flavi. Upon morphological and molecular characterization of the 20 isolates, 16 belonged to A. flavus, 2 to A. parvisclerotigenus and 2 to A. novoparasiticus. This is the first time that this latter species is isolated from food. Although most of these isolates were toxigenic on synthetic media, no AFB1 contamination was observed in these cassava samples. In order to determine the action of cassava on AFB1 synthesis, a highly toxigenic strain of A. flavus, was inoculated onto fresh cassava and despite a rapid development, no AFB1 was produced. The anti-aflatoxin property was observed with cassava from different geographical origins and on other aflatoxigenic strains of the section Flavi, but it was lost after heating, sun drying and freezing. Our data suggest that fresh cassava is safe regarding AFB1 contamination, however, processing may alter its ability to block toxinogenesis leading to secondary contamination.